La questione dell'uccisione 'umanitaria' nella pratica della baleneria: il confronto tra le diverse tecniche di caccia e le misure adottate dalla Commissione internazionale baleniera - Tani, I. (country:IT, 2006)
Whaling is considered to be one of the most violent of all hunting practices for the animals which are subject to it. The technical progress achieved in prey location systems and in processing carcasses on board factory ships has not been accompanied by an improvement in hunting techniques aimed at guaranteeing the animals a quicker bloodless death. The 58th Annual Meeting of the International Whaling Commission provided a stage for heated disagreement over the «humanitarian» treatment of these large sea mammals. (Even the bodies who are most sensitive to the moral question raised by the bloody killing of large whales failed to find an agreement, suggesting the need for serious reflection on the « speciesism » which characterises the ethical and legal approach to animal exploitation). The article contains a brief overview of the hunting techniques employed in oceans all over the world, from Greenland to the waters of the Antarctic, and the measures adopted by the International Whaling Commission over the last twenty years. The picture that emerges is a fairly critical one, showing no signs of improving as long as contingent economic considerations continue to prevail over ethical factors in the regulation of hunting techniques